THE ROLE OF THE ADAT MANTIR AS A VILLAGE JUDGE OF THE PEACE IN RESOLVING CRIMINAL CASES IN SUKAMARA DISTRICT, CENTRAL KALIMANTAN PROVINCE - Abdul Khair; Surya Sukti; Munib; Rabiatul Adawiyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research is grounded in the unique role of the mantir adat in a regency of Indonesia, who is not only authorized to resolve civil disputes but is also involved in the resolution of criminal cases. Therefore, the focus of this research is to explore why the mantir adat are involved in resolving their community's issues, even to the extent of handling criminal cases. It is qualitative descriptive research using observation, interviews, and documentation techniques. The research results concluded: First, In Sukamara Regency, the mantir adat (customary leaders) are involved in resolving community issues, even including criminal cases. This is because the people tend to prefer settling criminal matters through the mantir adat rather than in formal courts. The advantages of resolving cases through the customary mantir are (a) restorative justice, (b) lower costs; (c) fast and effective process, (d) the decisions made by the mantir adat are more accepted by the community, since the mantir adat, as village peace judge, has close relationships with the people and understands the social dynamics within the community. Second, the process of resolving criminal cases through the mantir adat, who functions as village judge, closely resembles the procedural stages of formal judicial institutions. Consequently, the decisions rendered by the mantir adat are regarded as equivalent in legitimacy to those issued by formal courts.